Studi Komparasi Metode Optimisasi Daya Pada Optical Ring Resonator - Herminarto Nugroho; Tamarindanara Prillyastraya Astarine; Anggerdini Wahyudi (JURNAL TEKNOLOGIA, 2020)
Optical Ring Resonators (ORRs) can be used as delay elements to form Optical Beamforming Network (OBFN). The ORR function is to ensure that the received signal will have the appropriate delay value so that the signal will be constructive. This study aims to compare the optimization method in obtaining the maximum power value of the magnitude of the phase shift and the optimal power coupling coefficient from the angle (θ) of the signal. The power criterion is based on the fact that the ideal power (desired) will be achieved when all phases of the different signals received by the antenna element are the same. By comparing the Sequential Quadratic Programming (SQP) and Simulated Annealing (SA) methods, the better optimization method can be found to determine the maximum power value of Optical Ring Resonator.